ATP1A1 de novo Mutation-Related Disorders: Clinical and Genetic Features - Zehong Lin; Jinliang Li; Taoyun Ji; Ye Wu; Kai Gao; Yuwu Jiang (Frontiers Media S.A., 2021)
Background:ATP1A1 encodes an α1 isoform of Na+/K+-ATPase, which is expressed abundantly in kidneys and central nervous system. ATP1A1 variants may cause Na+/K+-ATPase loss of function and lead to a wide spectrum of phenotypes. This study aims to summarize the clinical and genetic features of ATP1A1 de novo mutation-related disorders and explore the potential correlations between phenotypes and genotypes.Methods: We analyzed two new cases harboring novel de novo ATP1A1 variants and reviewed all reported cases.Results: Both our probands had developmental delay, patient 1 accompanied with sleep disorders, irritability, and patient 2 with refractory seizures. They each had a novel de novo heterozygous missense variant, c.2797G>A[p.Asp933Asn] (NM_000701) and c.2590G>A[p.Gly864Arg] (NM_000701) respectively. Four patients with de novo ATP1A1 variants have been reported in two previous papers. Among them, three patients had refractory seizures and one patient had complex hereditary spastic paraplegia (HSP). Therefore, all six patients had developmental delay, and four of them had epilepsy. All variants located in the transmembrane regions M3, M4, M7, and M8 of ATP1A1 protein. Four patients with mutations in M3 and M7 had more severe phenotypes, including developmental delay and epileptic encephalopathy, three of them with hypomagnesemia, whereas two patients with mutations in M4 and M8 had milder phenotypes, only with mild developmental delay, without seizures or hypomagnesemia. Correcting hypomagnesemia had not controlled those seizures.Conclusions: Two novel de novo ATP1A1 variants identified in two patients here enriched the genotypic and phenotypic spectrum of ATP1A1 mutation-related disorder. Our findings suggest that hypomagnesemia in this disorder might relate to more severe phenotype and indicate more severe Na+/K+-ATPase dysfunction. Variations in M3 and M7 transmembrane regions were related to more severe phenotype than those in M4 and M8, which suggested that variations in M3 and M7 might cause more severe ATP1A1 functional defect.